An environmental friendly electrode and extended cathodic potential window for anodic stripping voltammetry of zinc detection. (10th December 2016) - Dueraning, Anisah; Kanatharana, Proespichaya; Thavarungkul, Panote; Limbut, Warakorn
Graphical abstract: Abstract: This work reports on a novel polyeriochrome black T (poly(EBT) modified electrode for use as an environmentally-friendly electrode material that extends the cathodic potential window and improves the sensitivity and repeatability to detect zinc in industrial wastewater. The poly(EBT) film on the GCE surface was fabricated by electropolymerization. The surface morphology and electrochemical behavior of the modified electrode were characterized by scanning electron microscopy, fourier transform infrared spectroscopy and anodic stripping voltammetry. Under optimal conditions, the poly(EBT)/GCE exhibited a high hydrogen overvoltage (extended cathodic potential window). It provided a high sensitivity, a wide linear range (1.0 to 400.0 μg L −1 ), a low detection limit (0.9 μg L −1 ), had excellent repeatability and good recoveries (95% to 105%). This proposed modified electrode was applied to the determination of zinc in wastewater samples, and the results were consistent with those of an inductively coupled plasma atomic emission spectroscopy analysis.